Structural Color Filters Enabled by a Dielectric Metasurface Incorporating Hydrogenated Amorphous Silicon Nanodisks - Chul-Soon Park (Nature Portfolio, 2017)
Abstract It is advantageous to construct a dielectric metasurface in silicon due to its compatibility with cost-effective, mature processes for complementary metal-oxide-semiconductor devices. However, high-quality crystalline-silicon films are difficult to grow on foreign substrates. In this work, we propose and realize highly efficient structural color filters based on a dielectric metasurface exploiting hydrogenated amorphous silicon (a-Si:H), known to be lossy in the visible regime. The metasurface is comprised of an array of a-Si:H nanodisks embedded in a polymer, providing a homogeneously planarized surface that is crucial for practical applications. The a-Si:H nanodisk element is deemed to individually support an electric dipole (ED) and magnetic dipole (MD) resonance via Mie scattering, thereby leading to wavelength-dependent filtering characteristics. The ED and MD can be precisely identified by observing the resonant field profiles with the assistance of finite-difference time-domain simulations. The completed color filters provide a high transmission of around 90% in the off-resonance band longer than their resonant wavelengths, exhibiting vivid subtractive colors. A wide range of colors can be facilitated by tuning the resonance by adjusting the structural parameters like the period and diameter of the a-Si:H nanodisk. The proposed devices will be actively utilized to implement color displays, imaging devices, and photorealistic color printing.